Uji Linieritas Kalium Tiosianat (KSCN) Sebagai Indikator Kolorimetri Untuk Mendeteksi Konsentrasi Fe Pada Air - Azrul Fahmi; Widodo Budi Kurniawan; Anisa Indriawati (Jurusan Fisika, Universitas Bangka Belitung, 2022)
The method of testing water quality that is in great demand by researchers because it is practical and inexpensive, one of which is the colorimetric method. To detect the concentration of Fe using a colorimetric method used a colorimetric indicator such as potassium thiocyanate (KSCN). KSCN is a compound consisting of the elements potassium (K), sulfur (S), carbon (C), and nitrogen (N) which can produce an orange color when reacted with Fe. In this study, 20 variations of Fe solution were used with a concentration difference of 0.5 ppm starting from 0.5 ppm to 10 ppm and obtained a correlation coefficient of 0.9962 through the UV-Vis spectrophotometer test so that potassium thiocyanate (KSCN) can be used as a colorimetric indicator for detect the concentration of Fe in water.